Peningkatan Kompetensi Sumber Daya Insani (SDI) Melalui Internal Corporate Social Responsibility (ICSR) di PT BPRS Mitra Mentari Sejahtera Ponorogo - Qoyriyah; Ridho Rokamah (Falahiya: Journal of Islamic Banking and Finance, 2023)
Abstract: Competence is the ability to master and apply workplace knowledge, skills, and work attitudes. The Islamic banking industry in Indonesia is still experiencing several obstacles, one of which is the minimal aspect of the quantity and quality of human resources. This study aimed to determine efforts to increase human resource competence through implementing Internal Corporate Social Responsibility at BPRS Mitra Mentari Sejahtera Ponorogo. This type of research is field research with a qualitative approach. The techniques used are interviews, observation, and documentation. Based on research conducted at BPRS Mitra Mentari Sejahtera Ponorogo, the following results were obtained: 1) Indicators of HR competence, namely knowledge, skills, motives, attitude, and spirituality; 2) The implementation of ICSR has been carried out following the stages covering security and safety, employee human rights, training and development, the balance of work and life, and diversity in the work environment; 3) The impact of implementing ICSR is increasing the quality of service quality, competence, knowledge and expertise, spiritual, moral values, and work motives, as well as increasing the efficiency, effectiveness, and productivity of human resource performance which has an impact on increasing the number of market customers every month. Keywords: Competence, Human Resources, Internal CSR, Islamic Banking Abstrak: Kompetensi adalah kemampuan menguasai, menerapkan pengetahuan, keahlian dan sikap kerja ditempat kerja. Industri perbankan syariah di Indonesia masih mengalami beberapa kendala, salah satunya minim aspek kuantitas dan kualitas sumber daya manusia. Tujuan penelitian ini untuk mengetahui upaya peningkatan kompetensi sumber daya insani melalui penerapan Internal Corporate Social Responsibility di BPRS Mitra Mentari Sejahtera Ponorogo. Jenis penelitian ini adalah penelitian lapangan dengan pendekatan kualitatif. Teknik yang digunakan adalah wawancara, observasi dan dokumentasi. Berdasarkan penelitian yang dilakukan di BPRS Mitra Mentari Sejahtera Ponorogo, diperoleh hasil sebagai berikut: 1) Indikator kompetensi SDI yaitu knowledge, skill, motives, attitude dan spiritually; 2) Penerapan ICSR telah dijalankan sesuai tahapan meliputi keamanan dan keselamatan, HAM karyawan, training dan pengembangan, keseimbangan kerja dan hidup dan keragaman di lingkungan kerja; 3) Dampak penerapan ICSR yaitu meningkatkan mutu kualitas pelayanan, kompetensi pengetahuan dan keahlian, nilai moral spiritualitas, motif bekerja, serta meningkatkan efisiensi, efektifitas dan produktivitas kinerja sumber daya insani yang berdampak pada bertambahnya jumlah nasabah pasar disetiap bulan. Kata Kunci: Kompetensi, Sumber Daya Insani, CSR Internal, Perbankan Syariah